A revision of the endemic South African spider genus Austrachelas, with its transfer to the Gallieniellidae (Arachnida: Araneae) - Haddad, Charles R.; Lyle, Robin; Bosselaers, Jan; Ramirez, Martin J. (Zootaxa, 2009)
The endemic South African spider genus Austrachelas Lawrence, 1938 is revised. The type species, A. incertus Lawrence, 1938, and A. natalensis Lawrence, 1942, are redescribed, and their males described for the first time. Seven new species are described: A. bergi n. sp. (female only), A. kalaharinus n. sp. (male only), A. merwei n. sp. (both sexes), A. pondoensis n. sp. (both sexes), A. reavelli n. sp. (both sexes), A. sexoculata n. sp. (male only), and A. wassenaari n. sp. (both sexes). A cladistic analysis performed including Austrachelas and various species of the corinnid subfamilies Trachelinae, Castianeirinae, Corinninae and Phrurolithinae, and species from the Liocranidae, Gallieniellidae, Gnaphosidae and Lamponidae, suggests that Austrachelas is currently misplaced. Its transfer to the Gallieniellidae is proposed.